SIFAT VENIR DAN KAYU LAPIS SEMBILAN JENIS KAYU BERASAL DARI KALIMANTAN BARAT DAN JAWA BARAT - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper presents study result on the log peeling properties and the glueing, physical and mechanical properties of the veneer and plywood made from nine wood species are described in this paper. The result shows that all of the, logs could be peeled in cold condition. The average veneer shrinkage from green to oven dry moisture content was 7.00 % and veneer swelling from oven dry to air dry condition the average value was 3.39 %. The average thickness reduction due to pressing in plywood manufacturing was 3. 78 mm. The bonging strength of plywood from 8 wood species (89 %) conforms with the Indonesian standard for type II, 9 wood species (100 %) with Japanese standard and 9 wood species (100 %) with German standard. The average specific gravity of multiplex was 0.61 while the average specific gravity of trplex was 0.60. Bending strength. tensile strength and compression strength parallel to grain of triplex are higher than multiplex.